PENGURANGAN KECEPATAN PENGENDAPAN LUMPUR LAPINDO UNTUK MENINGKATKAN KAPASITAS SUNGAI PORONG - Suhudi Suhudi (Universitas Tribhuwana Tunggadewi, 2011)
Lapindo mud is a type mud classified as extremely unique because it is so quick to settle. The aims of this research was to determine the level of mud viscosity and flow rate in order to increase the disposal capacity in Porong River. The research was conducted in a laboratory soil mechanics and hydraulics ITN of Malang. The type mud is a type of sandy loam with specific gravity of 2.68 gr/cm3; average grain diameter of 0.0153 mm; 139.07 m wide river bed, 4.31 m/s maximum flow rate and 6.94 m/s minimum in which were difficult to move sediment so an effort was required for flushing, so that the tractive force that occurred (τ0) was 0.0183 kg/m2 < allowed from the allowable tension = 0.46 pon/feet2 or = 0.057 kg/m2. The result of this research was the addition of 2% chemicals (HCl) could help to reagent so as to break the clumping (flock) to the sedimentation process could be slowed down and distance of precipitation could be lengthened. Lapindo mud has quickly settled nature, due to molecular cohesion having dilatants nature meaning that it required high enough power to do the movements stirring the mud. Mud would have high viscosity (up) when performed with a large shearing force tension that causes turbulent mud moving. Nevertheless, there was no fast precipitation happen or deposition time was extended to Lapindo mud